SAT-616 Coexistence of Resistance to Thyroid Hormone Syndrome and Pituitary Granular Cell Tumor in a Taiwanese Young Lady Mimicking TSH Secreting Tumor - Lin, Yu-Yi (J Endocr Soc, 2019)
Background Resistance to thyroid hormone (RTH) syndrome is a rare disorder which presents as high free thyroid hormones with unsuppressed thyroid-stimulating hormone (TSH) secretion and diminished responsiveness to thyroid hormones by target organ. Appropriate diagnosis is crucial to avoid over-treatment with anti-thyroid drugs, radio-iodine ablation, and/or pituitary surgery. The aim of this report was to present the first case of RTH in Taiwan, who was misdiagnosed as TSH secreting tumor but later proved to have pituitary granular cell tumor instead. Clinical case A 33-year-old Taiwanese married woman was found to have elevated free T4: 3.92 ng/dL (normal: 0.8-1.9) and TSH: 5.82 μIU/mL (normal: 0.4-4.0) levels on pre-natal counseling for evaluation of palpitation and difficult conception in 2013. Besides mild tachycardia (heart rate: 98 beats per minute), she had no other symptoms and signs of hyperthyroidism. Propylthiouricil was prescribed by her gynecologist and discontinued one year later due to persistence of abnormal thyroid hormone levels under medication. Afterwards, she was referred to an endocrinologist and was told to have central hyperthyroidism based on negative thyroid autoantibodies, moderately enlarged homogenous thyroid glands on thyroid sonography, and a 1.2 cm right pituitary adenoma on sella magnetic resonance imaging (MRI). Endoscopic trans-phenoidal surgery for pituitary tumor removal was performed in May, 2017. Histopathology revealed granular cell tumors that were positive for S-100 protein and TTF-1 but negative for TSH, ACTH, GH and prolactin on immunohistochemical staining. In February 2018, she visited Taipei Veterans General Hospital due to persistence of abnormal thyroid hormone levels (free T4: 2.19 ng/dL; T3: 209 ng/dL, normal: 58-159; total T4 14.78 ug/dl, normal: 4.5-12.50; TSH 3.75 μIU/mL) after pituitary surgery. Post-operative sella MRI showed no residual pituitary tumor. After administration of 200 mcg of thyrotropin releasing hormone (TRH) intravenously, exaggerated TSH response was noted, with TSH levels showing 6.0, 24.7, 22.6, and 14.7 μIU/mL at 0, 20, 30, and 60 minutes, respectively, leading to the diagnosis of RTH. DNA sequencing of exons 4-10 of thyroid hormone receptor β gene revealed no mutation. As pregnancy was planned, Inderal 5mg thrice daily was used to lower T3 levels in case if a non-RTH fetus exists. Clinical lessons Although rare, RTH should be considered in the differential diagnosis of high thyroid hormone levels with unsuppressed TSH. The presence of a pituitary adenoma does not conclude a TSH secreting tumor, like our case. We suggest careful evaluation with functional and genetic testing prior to initiation of therapy in order to avoid unnecessary surgeries and medications. A favorable outcome generally follows a diagnosis of RTH. Special consideration needs to be taken in mothers with RTH harboring wild-type fetus.